Influence of Fe introduction method on gold state in NaY zeolite; International Journal of Modern Physics B; Vol. 19, № 15-17 - Smolentseva E.; Pestryakov A. N. Aleksey Nikolaevich; Bogdanchikova N.; Simakov A.; Avalos M.; Farias M.; Diaz J.; Gurin V.; Tompos A. (2005, 2005)
Special issue: Conference on Cluster Science and Nanotechnology; Nanjing, China, September 6-10, 2004; Lanzhou, China, September 12-15, 2004